Forests, water and mixed land use mosaics in developing countries: making research solutions effective - Spilsbury, M.J. (International Forestry Cooperation Agency, Ministry of Agriculture, Forestry and Fisheries, 2002)
This paper summarises some of the prevailing issues and challenges in relation to forests and water. It highlights some of the key constraints to the utilisation of existing knowledge. Hydrological processes may be well understood at a plot level, or for a single particular land use/landcover type at a catchment scale but become more uncertain at larger spatial scales or at smaller scales where the same processes operate across multiple land uses and management regimes. Most watershed management projects give little priority to research and monitoring, even though these are essential to effective watershed management and essential for establishing the efficacy of water management interventions. Given that interventions in mixed landscapes will be via multiple actors at a range of scales such monitoring feedback is essential to identifying, and reinforcing, those that are effective. Monitoring must track social, economic and biophysical variables that are useful and cost effective for management. The paper concludes that future research efforts should focus on how to maximise the provision of environmental services in mixed land use mosaics, and suggests how to improve research uptake and influence at policy levels since existing research has failed to sufficiently inform public policy debates. Consortium approaches to research that have close links to policy and development processes are required and should pay great attention to the factors and processes that influence research uptake in order to narrow the gulf between popular conventional wisdom, public policy and scientific knowledge.